Control and Inner exile of female educators during the Dictatorship of Primo de Rivera - Robles Sanjuan, Victoria; Rabazas Moreno, Teresa (Historia y Memoria de la Educación, 2022)
The aim of this article is to study the consequences of Primo de Rivera’s dictatorship on women educators, focusing our interest on repression and internal exile during this totalitarian period. Our study takes as its starting point the conceptual debate on inner exile as a consequence of totalitarian regimes and their repercussions on female educators. The analysis of the research shows the mechanisms of reaction of some female teachers to the control, local despotism and punitivism that was exercised over the teaching profession during this regime. At the same time, it has allowed us to demonstrate with some examples the oppressive context of the female teaching collective, contributing to the reconstruction of some trajectories during the inner exile of two teacher trainers: Gloria Giner and Concepción Alfaya.